Employee’s perception of corporate social responsibility – Evidence from the Czech Republic - Činčalová, Simona; Jeřábková, Elen (Eastern Review, 2021)
The importance of social responsibility has an everymore prominent position. This is since the world is increasingly interconnected and globalization is constantly moving forward. The aim of the paper is to analyse the activities of social responsibility of a selected company: Bosch, and then propose specific recommendations for further development of the company. It is based on analysis of company reports, interviews with managers and a questionnaire survey. The Bosch Group is a leading global supplier of technology and services. We focused on the plant in Jihlava, in the Czech Republic. The findings show that most employees know the concept of CSR and perceive it as a positive matter and want their employer to behave according to this concept. According to them, the greatest attention should be paid to the social pillar. The survey shows that the employees know the values of the company in which they work. In terms of communication with employees with regards to the activities of CSR, it is at a high level. Finally, recommendations are proposed, including ones concerning problems with transport, eco-labels, communication and employee support.